Implementation of Bilingual Learning to Develop Students’ Language Skills: Penelitian - Tiarnita Maria Sarjani Br. Siregar; Aldo Loviandri Sihombing; Elida Ronauli Saragi; Elsa Desima Sitorus; Sarah Artamevia Tamba (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The implementation of bilingual learning contributes significantly to the development of students’ language abilities through the integrated use of two languages. Literature indicates that bilingual instruction enhances listening, speaking, reading, and writing skills while also enriching students’ understanding of academic concepts taught in the classroom. The process of shifting between the first language (L1) and the second language (L2) has been shown to strengthen cognitive flexibility, executive functioning, and higher-order thinking skills. Pedagogical strategies such as translanguaging, linguistic scaffolding, the use of visual media, and the CLIL approach play essential roles in creating effective, communicative, and meaningful learning experiences. Beyond linguistic and cognitive benefits, bilingual education also positively influences students’ social and emotional development, including increased self-confidence, collaboration skills, and cultural sensitivity. However, its implementation still faces challenges such as limited teacher competence in managing two languages, insufficient learning materials, and the need for more systematic planning. Overall, bilingual learning provides great opportunities to shape students who are academically strong, cognitively adaptive, and socially inclusive.